2002
DOI: 10.1046/j.1365-2044.2002.02514.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood component use in critically ill patients

Abstract: SummaryThis prospective observational study was conducted to assess the current transfusion practice in critically ill patients. One thousand two hundred and forty-seven consecutive critically ill patients admitted between February 1999 and October 1999 were included in the study. Overall 666 (53%) patients were administered red cells. Transfused patients had signi®cantly higher intensive care unit mortality but also had higher Acute Physiology and Chronic Health Evaluation II scores and longer durations of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
2
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 18 publications
10
63
2
10
Order By: Relevance
“…Approximately 40% of the cohort received transfusions during the course of their ICU stay, and the mean pretransfusion hemoglobin level was 84 g/l [1]. A similar study in the United Kingdom confirmed these observations [13]. Unlike other cross-sectional studies, we observed that RBC transfusions in our study were less frequent than previously reported (21 vs. 40–50%) [1,2,14].…”
Section: Discussioncontrasting
confidence: 53%
“…Approximately 40% of the cohort received transfusions during the course of their ICU stay, and the mean pretransfusion hemoglobin level was 84 g/l [1]. A similar study in the United Kingdom confirmed these observations [13]. Unlike other cross-sectional studies, we observed that RBC transfusions in our study were less frequent than previously reported (21 vs. 40–50%) [1,2,14].…”
Section: Discussioncontrasting
confidence: 53%
“…In our study 56.9% of the transfused units were packed red cells, 22.7% fresh frozen plasma and 20.4% platelet concentrates. Similarly Rao et al, [10] assessed transfusion practice in 1,247 critically ill patients and showed that 53% were administered red cells, 22% fresh frozen plasma and 16% platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Bu konuyla ilgili pek çok çalışma bildirilmiştir (14)(15)(16)(17)(18)(19)(20)(21)(22) Bilindiği gibi dokulara oksijen sunumu; Hb konsantrasyonu, Hb değerinin saturasyon yüzdesi ve kalp debisine bağlıdır. Oksijen sunumundaki düşüş; dokudaki oksidatif metabolizmayı engeller ve anaerobik metabolizmaya kaymaya neden olur.…”
Section: Discussionunclassified